Characteristics of, employment and training in commercial restaurants in Makati - Catral, Ma. Lourdes D.; Acasio, Florecita B. (1975)
This is a study of 113 commercial restaurants in Makati licensed by the municipal government to operate as of June 1974. Data on characteristics of the restaurant and the manager were obtained by means of questionnaires administered to the restaurant managers. Data on characteristics of employment and training were obtained through interviews with the personnel managers of the restaurants. Majority of the commercial restaurants in Makati were owned by single proprietors and manager owned. Restaurants at the commercial center catered primarily to foreign tourists and office employees while restaurants at the main roads and side streets catered primarily to office employees. The number and seating capacity of food outlets wee greater in restaurants at the commercial center than for those at the main roads and side streets. Food outlets in the restaurants were open an average of 12 hours a day. Owner/manager was the most common job title used to refer to the restaurant manager. More managers of the restaurants of the commercial center were young, and had higher level of education than in restaurants at the main roads and side streets. In the commercial restaurants of Makati, the highest mean monthly starting salary was paid for positions concerned with seating and greeting customers and supervising waiters; lowest was that for positions concerned with washing dishes, polishing silverware and disposing garbage and positions concerned with setting tables, serving food and drinks. The mean monthly starting salaries were higher in restaurants at the commercial center than for those at the main roads and side streets. The overall rate of labor turnover for supervisory positions was at six percent while that for non-supervisory positions was at 10 percent. The highest rate of labor turnover was for supervisory positions concerned with washing dishes, polishing silverware and disposing garbage at 42,8 percent and for non-supervisory positions concerned with greeting and seating customers, at 66.7 percent. There was no labor turnover reported for supervisory positions concerned with cutting and preparing meat or fish for cooking and non-supervisory positions concerned with mixing and dispensing alcoholic drinks. Majority of the restaurants in Makati did not provide employee training. Training conducted was mainly on-the-job and of the informal type. The need for training was foremost in the area of food preparation and service. The position for which training was urgently needed was waiter. Findings revealed the need for a better system of defining and classifying commercial restaurants as a basis for licensing; the predominance of small owner-managed restaurants in Makati; the lack of appropriate education and training of the restaurant managers; the need for a uniform system of classification of job titles and a standardization of the salary structure in the restaurants; and the need for more and well-organized training programs for restaurant employees.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Restaurants, lunch rooms, etc. -- Philippines -- Makati, Rizal; Restaurants, lunch rooms, etc -- Employees -- Makati, Rizal